State Strategies in Multi-Ethnic Territories: Explaining Variation in the Former Soviet Union and Eastern Bloc. Issue 2 (12th February 2013) - Daly, Sarah Zukerman
<x content-type="archive" xml:space="preserve">Abstract</x> After the collapse of the Soviet bloc, its twenty-seven successor states were charged with devising policies with respect to their ethnic minorities. This shock enables an analysis of the conditions that render states more likely to repress, exclude, assimilate or accommodate their minorities. One would anticipate that groups that are most 'threatening' to the state's territorial integrity are more likely to experience repression. However the data do not validate this expectation. Instead, the analysis suggests that minority groups' demographics and states' coercive capacities better account for variation in ethnic minority policies. While less robust, the findings further indicate the potential importance of lobby states and Soviet multinational legacies in determining minority rights. The results have implications for ethnic politics, human rights, nationalism, democratization and political violence.